The Debt‐Equity Spread - CHEN, HUI; CHEN, ZHIYAO; LI, JUN (Journal of Finance, 2026)
ABSTRACT We propose a measure of the valuation gap between debt and equity—debt‐equity spread (DES)—based on the difference between actual and equity‐implied credit spreads. DES predicts cross‐sectional stock and bond returns in opposite directions. This predictability is unique compared to existing mispricing measures and cannot be explained by exposures to various risk factors. High‐DES firms are more likely to issue equity and retire debt, and have more insider equity selling. These findings are consistent with DES capturing relative mispricing between debt and equity, and provide empirical support for the model of partially segmented markets in Greenwood, Hanson, and Liao (2018, Review of Financial Studies 31, 3307–3343).